1999
DOI: 10.1091/mbc.10.11.3815
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Domains Enriched in RNA 3′-processing Factors Associate with Coiled Bodies and Histone Genes in a Cell Cycle–dependent Manner

Abstract: Nuclear domains, called cleavage bodies, are enriched in the RNA 3Ј-processing factors CstF 64 kDa and and CPSF 100 kDa. Cleavage bodies have been found either overlapping with or adjacent to coiled bodies. To determine whether the spatial relationship between cleavage bodies and coiled bodies was influenced by the cell cycle, we performed cell synchronization studies. We found that in G1 phase cleavage bodies and coiled bodies were predominantly coincident, whereas in S phase they were mostly adjacent to each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 57 publications
3
43
0
Order By: Relevance
“…In Drosophila, coilin is absent and there is a functional distinction between Cajal bodies (CBs) and histone locus bodies (HLBs) (Liu et al, 2006). Similarly, a distinction has been made between cleavage bodies, which contain histone gene loci, and adjacent Cajal bodies (Schul et al, 1999). The interpretation of in situ microscopy data of Cajal bodies and related structures is further complicated by the technical limitation that no more than three or four components can be visualized at any one time.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, coilin is absent and there is a functional distinction between Cajal bodies (CBs) and histone locus bodies (HLBs) (Liu et al, 2006). Similarly, a distinction has been made between cleavage bodies, which contain histone gene loci, and adjacent Cajal bodies (Schul et al, 1999). The interpretation of in situ microscopy data of Cajal bodies and related structures is further complicated by the technical limitation that no more than three or four components can be visualized at any one time.…”
Section: Discussionmentioning
confidence: 99%
“…During G1 phase the two processing factors in addition to being evenly distributed throughout the nucleoplasm are concentrated in Cajal bodies (Schul et al, 1999). Interestingly, in S phase CstF-64 and CPSF-100 redistribute to separate structures called the cleavage bodies, which in contrast to Cajal bodies precisely co-localize with the histone gene loci and contain nascent histone transcripts.…”
Section: The Role Of Cajal Bodies In Histone Gene Expressionmentioning
confidence: 99%
“…It is possible that the cleavage bodies, although not always easily distinguishable from closely associated Cajal bodies, also contain U7 snRNP and other essential processing factors, and constitute the true sites for 3' end processing of histone premRNAs. Notably, the identification of CstF-64 and CPSF-100 in the close proximity to the histone gene loci for the first time suggested that these two known cleavage/polyadenylation processing factors may also be involved in formation of the nonpolyadenylated histone mRNAs (Schul et al, 1999).…”
Section: The Role Of Cajal Bodies In Histone Gene Expressionmentioning
confidence: 99%
“…Cleavage bodies, nuclear structures occupied by RNA 3Ј-processing factors, have been shown to contact or to overlap Cajal bodies (45). Cleavage bodies are also observed in only a subset of asynchronously growing cells, since they disappear during the G 2 phase of the cell cycle (46). The association of Cdk2-cyclin E complexes with Cajal bodies is also regulated in a cell cycle-dependent manner (30).…”
Section: Discussionmentioning
confidence: 99%